ANALISIS MISKONSEPSI SISWA DALAM PEMBELAJARAN FISIKA MATERI FLUIDA STATIS MENGGUNAKAN METODE CERTAIN OF RESPONSE INDEX (CRI) DI SMAN 7 PEKANBARU - Valina Yolanda; Fakhruddin '; Yennita ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the misconception experienced by students in physics learning on static fluid material using Certain of Response Index (CRI) method at SMAN 7 Pekanbaru. This research was conducted from March to July 2017 with the subject of research is all students of class X in SMAN 7 Pekanbaru as many as 106 students. The type of research conducted is survey research. In this study, the data obtained were primary data and the instruments used to measure student misconceptions on static fluid materials were misconception tests. This misconception test consists of 20 items of multiple choice and is accompanied by CRI columns for each answer. CRI value shows the level of confidence of students in answering questions. The data have been analyzed descriptively. Based on the data analysis, it was found that the mean misconception of students on static fluid material was 42%, with misconceptions on each of the static fluid submissions such as hydrostatic pressure, Pascal's law, Archimedes law and surface tension, respectively: 41% 42%, 46% and 38%. Thus it can be concluded that the misconception experienced by the students of class X of SMAN 7 Pekanbaru on static fluid material is still quite high and the highest percentage of student misconception is found in the submateri Archimedes law.Keywords : Misconception, static fluid, CRI (certain of response index)